Trigonometric Identities

Geometry Level 2

Let α \alpha and β \beta be the values of θ \theta that satisfy sin θ + 3 cos θ = 0 \sin \theta + \sqrt{3} \cos \theta = 0 , where 0 θ 2 π 0 \leq \theta \leq 2\pi . What is the value of tan 2 ( α + β ) \tan^2\left(\alpha + \beta\right) ?


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Arron Kau Staff
May 13, 2014

Solution 1: Substituting θ = π 2 \theta = \frac{\pi}{2} gives 1 + 0 = 0 1 + 0 = 0 , which is a contradiction. Substituting θ = 3 π 2 \theta = \frac{3\pi}{2} gives 1 + 0 = 0 -1 + 0 = 0 , which is a contradiction. Thus θ π 2 , 3 π 2 \theta \neq \frac{\pi}{2}, \frac{3\pi}{2} , which implies that cos θ 0 \cos \theta \neq 0 , and so we can divide the equation through by cos θ \cos \theta . So, we have tan θ + 3 = 0 \tan \theta + \sqrt{3} = 0 tan θ = 3 \Rightarrow \tan \theta = -\sqrt{3} . Since α \alpha and β \beta satisfy the given equation, thus tan α = tan β = 3 \tan \alpha = \tan \beta = - \sqrt{3} .

Using the sum of angles formula for tan \tan , we have

tan ( α + β ) = tan ( α ) + tan ( β ) 1 tan α tan β = 3 3 1 ( 3 ) ( 3 ) = 2 3 1 3 = 3 \begin{aligned} \tan \left(\alpha + \beta \right) &= \frac{\tan(\alpha) + \tan(\beta)}{1 - \tan\alpha \tan \beta} \\ &= \frac{-\sqrt{3} - \sqrt{3}}{1 - (-\sqrt{3})(-\sqrt{3})} \\ &= \frac{-2\sqrt{3}}{1 - 3} \\ &= \sqrt{3}\\ \end{aligned}

Hence tan 2 ( α + β ) = 3 \tan^2\left(\alpha + \beta\right)= 3 .

Solution 2: As shown in Solution 1, we have tan θ = 3 \tan \theta = - \sqrt{3} .

From the special right triangle 1 : 3 : 2 1: \sqrt{3}: 2 , we have tan ( π 3 ) = 3 \tan \left(\frac{\pi}{3}\right) = \sqrt{3} . Since tan \tan is an odd function, so tan ( π 3 ) = 3 \tan \left(-\frac{\pi}{3}\right) = -\sqrt{3} . tan \tan also has a period of π \pi , so 3 = tan ( π 3 + k π ) -\sqrt{3} = \tan \left(-\frac{\pi}{3} + k\pi \right) , where k k is an integer. Since 0 θ 2 π 0 \leq \theta \leq 2\pi , thus k = 1 , 2 k = 1,2 are the only possibilities and we get α = π 3 + π = 2 π 3 \alpha = -\frac{\pi}{3} + \pi = \frac{2\pi}{3} and β = π 3 + 2 π = 5 π 3 \beta = -\frac{\pi}{3} + 2\pi = \frac{5\pi}{3} .

Therefore tan ( α + β ) = tan ( 2 π 3 + 5 π 3 ) = tan ( π 3 ) = 3 \tan\left(\alpha + \beta\right) = \tan\left(\frac{2\pi}{3} + \frac{5\pi}{3}\right) = \tan\left(\frac{\pi}{3}\right) = \sqrt{3} . Hence tan 2 ( α + β ) = 3 \tan^2\left(\alpha + \beta\right) = 3 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...